Assessment of Ecological Change Due To Cyclone Using Remote Sensing Technique (Journal of Bangladesh Institute of Planners, 2015)
Ecology in coastal area of Bangladesh is affected by several natural hazards like cyclones, coastal flooding, tidal surges, salinity and other phenomenon. The ecological change of this area is mainly attributed to the periodic cyclones caused by deep depression formed over the Bay of Bengal. This research is carried out to measure the ecological change of cyclone affected costal area in Bangladesh using two key factors, named vegetation and temperature. To assess it, MODIS Global Disturbance Index (MGDI) method has been used for considering recent cyclone SIDR and AILA using time-series terra MODIS data between the periods 2005 to 2011. Raw MODIS data has been processed by re-projection and atmospheric correction. Enhanced Vegetation Index (EVI) and Land Surface Temperature (LST) have also been derived to determine the MGDI analyzing the variation of vegetation and temperature. It is found from the research that cyclones cause ecological change in the coastal area. Severe ecological disturbance has been found on the Sundarban area of Khulna, because of SIDR in 2007. It also had effects in Bagerhat, Barguna, Patuakhali and Pirojpur. In 2009, another cyclone, AILA causes severe ecological disturbance on Satkhira district and some part of Khulna district. However, this study provides a baseline to prioritize measures for reducing the ecological disturbance due to cyclone.Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 175-186